CENTRAL VENOUS CATHETERIZATION IN SURGICAL PATIENTS: A PROSPECTIVE EVALUATION OF INDICATIONS AND COMPLICATIONS (Asian Journal of Medical Research and Health Sciences, 2026)
Introduction: Central venous catheterization (CVC) is an essential procedure in surgical practice, providing reliable venous access for hemodynamic monitoring, fluid resuscitation, administration of vasoactive medications, total parenteral nutrition, and renal replacement therapy. Despite its clinical importance, CVC insertion is associated with mechanical, infectious, and thrombotic complications that may adversely affect patient outcomes. Objectives: To evaluate the indications for central venous catheterization and determine the incidence and pattern of early and late catheter-related complications among surgical patients in a tertiary care teaching hospital. Methodology: This descriptive cross-sectional observational study was conducted in the Department of General Surgery, Calcutta National Medical College & Hospital, Kolkata, over one year (June 2023–May 2024). A total of 172 consecutive surgical patients aged more than 12 years who required central venous catheterization were included. Demographic characteristics, indications for catheterization, insertion site, catheter duration, and procedure-related complications were recorded prospectively. Data were analyzed using SPSS version 27.0, and statistical significance was considered at p